Ribonuclease activity of buckwheat plant (Fagopyrum esculentum) cultivars with different sensitivities to buckwheat burn virus - Y. R. Sindarovska; O. I. Guzyk; L. V. Yuzvenko; O. A. Demchenko; L. F. Didenko; O. I. Grynevych; M. Ya. Spivak (The Ukrainian Biochemical Journal, 2014)
Ribonucleases (RNases) are present in base-level amounts in intact plants, but this level is able to increase greatly under stress conditions. The possible cause for such an increase is protection against plant RNA-virus attack. Buckwheat burn virus (BBV) is a highly virulent pathogen that belongs to Rhabdoviridae family. In our study, we have analyzed the correlation between RNase activity and resistance of different buckwheat cultivars to BBV infection. Two cultivars, Kara-Dag and Roksolana, with different sensitivities to BBV have been used. Kara-Dag is a cultivar with medium sensitivity to virus and Roksolana is a tolerant cultivar. It has been shown that the base level of RNase activity in Roksolana cultivar was in most cases higher than the corresponding parameter in Kara-Dag cultivar. Both infected and uninfected plants of Roksolana cultivar demonstrated high RNase activity during two weeks. Whereas infected plants of Kara-Dag cultivar demonstrated unstable levels of RNase activity. Significant decline in RNase activity was detected on the 7th day post infection with subsequent gradual increase in RNase activity. Decline of the RNase activity during the first week could promote the virus replication and therefore more successful infection of upper leaves of plants. Unstable levels of RNase activity in infected buckwheat plants may be explained by insufficiency of virus-resistant mechanisms that determines the medium sensitivity of the cultivar to BBV. Thus, plants of buckwheat cultivar having less sensitivity to virus, displayed in general higher RNase activity.